Mathematics-I:calculus and linear algebra,for computer science & engineering students only - Bhui,Bikas Chandra (Vikas Publishing House Pvt. Ltd, 2019)
Mathematics-I:calculus and linear algebra,for computer science & engineering students only / Bhui,Bikas Chandra. -- Kolkata: Vikas Publishing House Pvt. Ltd., 2019 510 B575 V1 No. of Copies : 1